Smart Irrigation Pump Design Building Range Using Arduino Atmega 328 - Silaban, Ismael Widodo; Sembiring Maha, Denny Hasminta; Nainggolan, Winner Parluhutan (Universitas Harapan Medan, 2024)
The integration of technology into agriculture has become increasingly prevalent, with smart irrigation systems emerging as a crucial tool for sustainable crop management. This research focuses on the design and implementation of a smart irrigation pump system using Arduino ATMEGA328 microcontroller, aiming to optimize water usage and enhance crop yields. The system utilizes a combination of sensors, actuators, and control logic to automate irrigation processes and adapt to changing environmental conditions. The device can also be used on surface irrigation systems because it can monitor the surface of the container in the water pad, so that the water is not wasted in vain because there is no control system, because the prototype device is running well. With an average accuracy rate of 98.3%.Arduino ATMEGA 328